Dealing with pandemics: An investigation of the effects of COVID-19 on customers' evaluations of hospitality services. (August 2021) - Hu, Feng; Teichert, Thorsten; Deng, Shengli; Liu, Yong; Zhou, Guotao
Abstract: The hospitality industry is highly vulnerable to pandemics. However, little is known about how pandemics alter travelers' evaluations of hospitality services. Therefore, this study investigates the changes in travelers' expectations and perceptions of hotel services during different stages of the novel coronavirus 2019 (COVID-19) pandemic. 98, 163 Chinese hotel reviews were collected and scrutinized via text mining and sentiment analysis techniques to derive new implications for service optimization. The results reveal shifts in consumers' evaluations well beyond hygienic requirements. Insights obtained from this research can help guide hospitality practice in organizing its priorities during acute pandemic situations and adjusting to possibly longer-lasting shifts in consumer preferences. Highlights: Travelers' online evaluations of hotel services are compared across different phases of the COVID-19 pandemic. Shifts in the importance travelers place on different hotel services are revealed through text mining of online reviews. Changes in travelers' perceptions of service performance are evaluated via sentiment analysis of online reviews. A comparative analysis summarizes changes in travelers' evaluations of hotel services across the COVID-19 pandemic. Novel insights for service optimization can help direct hospitality practice during the COVID-19 pandemic.